Stimulation of younger adolescents to self-realization in extracurricular cognitive activities (Pedagogy of Higher and Secondary Education, 2012)
Ivanova O. V. Stimulation of younger adolescents to self-realization in extracurricular cognitive activities.Methods of stimulating adolescences to self-realization in after-classes studying activities contributed developing studying interest, thinking, creativity and self-realisation.
Keywords: young adolescence; after-classes studying activity; studying interest